Pelatihan Self Management Untuk Meningkatkan Disiplin Belajar Siswa - Wulan Saputri Anjani; Cucu Arumsari; Aam Imaddudin (Journal of Innovative Counseling : Theory, Practice, and Research, 2020)
. This research is motivated by a phenomenon that develops among students related to discipline in the learning process. The results showed that the discipline of learning had an effect both directly and indirectly on the success of the learning process, affecting the improvement of learning achievement, learning outcomes, and motivation to learn so that there was an interest to be developed. Guidance and counseling have an important role both in anticipating and healing for students who have low learning discipline. One way to improve learning discipline is by applying self management training. The general objective of this study was to obtain an empirical picture of the effectiveness of self management training in improving student learning discipline in Class XI of SMA Negeri 2 Tasikmalaya in the 2018/2019 Academic Year, totaling 218 students. The study was conducted with a non equivalent control group design research design. The instrument used was a learning discipline questionnaire. The data analysis technique used the t-test formula and the SPSS 16.00 for windows program to measure the two-pair difference test. The results showed that in general the discipline of student learning in Class XI of SMA Negeri 2 Tasikmalaya was in the moderate category. Self management training is effective in improving student learning discipline.